UPAYA GURU PAUD MELAKSANAKAN PEMBELAJARAN TATAP MUKA DI RUMAH (Studi Kasus Guru Kelompok B TK Negeri Pembina Pontianak Timur) - Dessy Natalia; Fadillah Fadillah; Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the teacher's efforts to teach the social, emotional and language aspects of children at home. The method used is descriptive with a qualitative type of case study using observation, interview, and documentation techniques. The data sources consisted of 18 people. The results showed that the teacher's efforts to teach children at home were carried out by planning, implementing and designing child development assessments that were very visible when all these limitations were present in the current pandemic period, thus giving rise to ideas and maximum efforts in teaching. The first meeting with learning materials for children to work in groups, the second meeting is does not hurt and do good to God's creatures and adapting to the environment, the third meeting is about children knowing ornamental plants, the growth of preserving plants, the fourth meeting is living animals in fresh water, tell stories about children's experiences. Emotional social aspects include designing, obeying the rules, also through playing children willing to share, patiently waiting their turn and providing an assessment of children's development. The language aspect includes designing, implementing learning as outlined in teaching materials with storytelling, lecturing and prayer memorization methods.Keywords: Teachers' efforts, Learning Implementation, At Home